Outcomes of Vitrectomy in Pediatric Retinal Detachment with Proliferative Vitreoretinopathy - Robert Rejdak; Dominika Nowakowska; Katarzyna Wrona; Ryszard Maciejewski; Anselm G. Junemann; Katarzyna Nowomiejska (Journal of Ophthalmology)
Aim. To report outcomes of pars plana vitrectomy (PPV) in pediatric retinal detachment (RD) with proliferative vitreoretinopathy (PVR), complications, factors influencing the final anatomical and functional results. Methods. Retrospective consecutive case series of 14 eyes. Average postoperative follow-up period was 34 months. Results. Mean age of patients was 10 years; eleven patients (79%) were males. The most common etiology was trauma (57%), the second—myopia (36%) and one case of uveitis (7%). At the day of presentation, the best-corrected visual acuity (BCVA) was worse than hand motion (50%); macula was detached in 86% of cases. Simultaneous PPV and phacoemulsification with intraocular lens (IOL) implantation were performed in 12 cases (86%). The most common endotamponade during PPV was silicone oil (93%). Anatomic reattachment was accomplished in 86% of cases. Final BCVA was equal or better than 0.1 in 50% of patients. The postoperative complications were found in 5 eyes (36%). Conclusion. Complete PPV was allowed for anatomically reattached retina and preserved vision in pediatric complex RD with PVR. However, visual outcomes were not satisfactory. Preserving vision in children with RD is of great importance for their future motor and intellectual development. This trial is registered with ClinicalTrials.gov Identifier: NCT03208205.